MIDDLE TRIASSIC (LADINIAN) DEEP-WATER SEDIMENTS IN SICILY. NEW FINDINGS FROM THE MADONIE MOUNTAINS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
A section of carbonate megabreccias grading upward to deep-water Daonella limestones is described from the locality of Sant’Otiero, near Petralia Sottana, in the Madonie Mountains (Sicily). The megabreccia mainly consists of neritic elements containing dasycladalean algae (Diplopora annulatissima Pia) along with benthic foraminifers and problematics. The overlying calcilutitic strata are characterized by lumachella intercalations containing the bivalve Daonella tyrolensis Mojsisovics suggesting an early Late Ladinian (Protrachyceras longobardicum ammonoid zone) age. We informally name the Daonella limestone as the calcare di Sant’Otiero (Sant’Otiero limestone). The Daonella limestones along with the neritic megabreccia extraclasts with Diplopora annulatissima represent a previously unknown component of the pre-Carnian stratigraphy from the paleo-Alpine Sicily.
Keywords: Triassic; Ladinian; Sicily; Daonella; Deep-water limestones; Stratigraphy; Paleontology